A new tool for evaluating forages - L.H. Harbers; F.K. Brazle; Clenton E. Owensby (Kansas Agricultural Experiment Station Research Reports, 1977)
The scanning electron microscope has been used to observe the digestion of alfalfa hay and warm- and cool-season grasses. Photomicrographs show that leaves of all species are digested by bacteria and protozoa attacking either the upper part of the leaf or exposed edges; lower leaf surfaces are never attacked. Intake of a forage depends on how rapidly rumen bacteria and protozoa can enter the upper leaf surface and digest underlying material (mesophyll) leaving most of the highly lignified nutrient-carrying vessels (vascular tissue) undigested.
Keywords: Report of progress (Kansas State University. Agricultural Experiment Station); 291; Cattlemen' s Day; 1977; Beef; Intake; Alfalfa hay; Forage